Identity brand avoidance: How is it manifested in social media? - CHAN KAO CHUNG, Cindy (2011)
Existing research on brand symbolic consumption mainly focuses on brand approach; the phenomenon being explained by the theory of self congruity, i.e. consumers would approach brands whose image is congruent to their actual or ideal self. On the other hand, identity brand avoidance, has been object of less attention. The scarce research dedicated to this field essentially revolves around the causes of identity brand avoidance, i.e. when consumers have a positive image of themselves and a negative image of a brand, they would avoid the brand.